A sustainable programme to prevent falls and near falls in community dwelling older people: results of a randomised trial. Issue 3 (1st March 2000) - Steinberg, Margaret; Cartwright, Colleen; Peel, Nancye; Williams, Gail
Abstract : STUDY OBJECTIVE: In the causative mechanism of falls among older community dwellers, slips and trips have been found to be significant precursors. The purpose of the two year trial was to assess the effectiveness of multi-component interventions targeting major risk factors for falls in reducing the incidence of slips, trips and falls among the well, older community. DESIGN: Four groups with approximately equal numbers of participants were randomly allocated to interventions. The prevention strategies included education and awareness raising of falls risk factors, exercise sessions to improve strength and balance, home safety advice to modify environmental hazards, and medical assessment to optimise health. The interventions combined the strategies in an add on approach. The first intervention group receiving the information session only was regarded as the control. The outcome of interest was the occurrence of a slip, trip or fall, monitored prospectively using a daily calendar diary. PARTICIPANTS AND SETTING: Two hundred and fifty two members of the National Seniors Association in the Brisbane district agreed to participate. National Seniors clubs provide a forum for active, community dwelling Australians aged 50 and over to participate in policy, personal development and recreation. MAIN RESULTS: Using Cox's proportional hazards regression model, adjusted hazard ratios comparing intervention groups with the control ranged from 0.35 (95% CI 0.17, 0.73) to 0.48 (0.25, 0.91) for slips; 0.29 (0.16, 0.51) to 0.45 (0.27, 0.74) for trips; and 0.60 (0.36, 1.01) to 0.82 (0.51, 1.31) for falls. While calendar monitoring recorded outcome, it was also assessed as a prevention strategy by comparing the intervention groups with a hypothetical non-intervened group. At one year after intervention, reductions in the probability of slips, trips and falls (61(95%CI 54, 66)%; 56 (49, 63)%; 29 (22, 36)% respectively) were demonstrated. CONCLUSIONS: This study makes an important contribution to the priority community health issue of falls prevention by showing that effective, sustainable, low cost programmes can be introduced through community-based organisations to reduce the incidence of slips, trips and falls in well, older people.